An eﬃcient deep learning approach for detecting lung disease from chest X-ray images using transfer learning and ensemble modeling - Sagor, Mostofa Kamal; Jahan, Ishrat; Chowdhury, Susmita; Ansary, Rubayet (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.